Desarrollo de la competencia sociocultural entre estudiantes de maestría como parte del curso “La Cultura de los Países Romano-Germánicos” - Bakmansurova, Alla Bariyevna (2022)
The objective of the research is to examine the features of socio-cultural competence and its development among master students studying a second foreign language. To reach the objective, the following tasks should be solved: to define socio-cultural competence, to analyze its components / its content; to analyze an example of a training course for master students, in which the formation and development of socio-cultural competence is expected; to conduct a survey among students; to analyze the empirical data obtained; to make a conclusion about the degree of awareness / understanding of the need to develop socio-cultural competence when learning a (second) foreign language. The proposed study is theoretically significant to some degree for methodological science (the section devoted to communicative competence and its components) and is practically valuable since it describes the specific experience of the formation and development of the competence being studied in higher education.